2022
DOI: 10.1177/21676968221117421
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Racism, Depressive Symptoms, Drinking to Cope Motives, and Alcohol Use Severity Among Asian American Emerging Adults

Abstract: The COVID-19 pandemic has incited widespread anti-Asian racism, which is linked to numerous behavioral health consequences including depressive symptoms. As racism-induced depressive symptoms are linked to coping-related alcohol use and because alcohol-related problems represent a significant public health concern in this population, we investigated whether COVID-19 racism predicted alcohol use severity through depressive symptoms and drinking to cope motives among Asian American emerging adults ( N = 139; Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Among Asian American youth, boys are more likely to be peer-victimized, especially physically (Huang & Vidourek, 2019). Large-scale studies including this group have linked peer-victimization with substance use (Stone & Carlisle, 2017) and suicidality (Wang et al, 2018), both of which are significant public health problems for AAM (Hai et al, 2021; Keum & Choi, 2022; Ramchand et al, 2021). Moreover, victimized AAM may be stereotyped as “model victims” (Takahashi, 2020) and dismissed within and across communities and institutions, potentially exacerbating help-seeking disparities (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among Asian American youth, boys are more likely to be peer-victimized, especially physically (Huang & Vidourek, 2019). Large-scale studies including this group have linked peer-victimization with substance use (Stone & Carlisle, 2017) and suicidality (Wang et al, 2018), both of which are significant public health problems for AAM (Hai et al, 2021; Keum & Choi, 2022; Ramchand et al, 2021). Moreover, victimized AAM may be stereotyped as “model victims” (Takahashi, 2020) and dismissed within and across communities and institutions, potentially exacerbating help-seeking disparities (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we observed that the perceived burdensomeness and thwarted belongingness scores in the current sample were higher than the mean perceived burdensomeness (7.45) and thwarted belongingness (19.65) scores reported in a previous study by Hollingsworth et al (2017) . A recent study by Keum and Choi (in press) found that anti-Asian COVID racism was linked to increased depressive symptoms and alcohol use to cope with the distress among Asian American emerging adults. Given that the anti-Asian dynamic may be pervasive and explicit in the current sociopolitical climate in the United States, perceived burdensomeness may have been a robust mediator between online racism and suicide ideation among Asian individuals in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during the COVID-19 pandemic, anti-Asian hate crimes and discrimination have spread both offline and online (Chou et al, 2021). In addition to encountering offline anti-Asian racial discrimination and hate crimes (Keum & Choi, 2022), Asian Americans have reported experiencing increased online victimization (Patchin & Hinduja, 2023) and vicarious exposure to traumatic anti-Asian hate content (e.g., mass shootings, hate crimes; Gover et al, 2020). For an Asian American individual reporting distress from experiencing offline anti-Asian racial discrimination, their stress may be further exacerbated by exposure to online racism.…”
Section: The Joint Impact Of Online and Offline Racismmentioning
confidence: 99%